Compost maturity and plant response in community-based compost systems from Bali, Indonesia - PUTU OKI BIMANTARA; I MADE ADNYANA; NI LUH KARTINI; I GUSTI NGURAH MADE PRABHASWARA (Asian Journal of Agriculture, 2026)
Abstract. Bimantara PO, Adnyana IM, Kartini NL, Prabhaswara IGNM. 2026. Compost maturity and plant response in community-based compost systems from Bali, Indonesia. Asian J Agric 10 (1): g100176. https://doi.org/10.13057/asianjagric/g100176. This present study focused on determining the quality of compost, its maturity, and the reaction of plants to different types of compost produced by community-run and municipal waste disposal centers in Bali, Indonesia. Compost samples were gathered from four locations of waste disposal facilities, specifically from Panca Lestari, Padang Tegal, PDU DLHK Denpasar, and Kedonganan. The quality of compost was determined according to the SNI 19-7030-2004, consisting of organic carbon, total nitrogen, C/N ratio, organic matter, pH, moisture, and physical aspects. The experiment was conducted in a greenhouse using Ipomoea reptans in factorial randomized block design with four levels of compost treatments, i.e., K0=control, K1=1.0 kg polybag-¹, K2=1.3 kg polybag-¹, and K3=1.6 kg polybag-¹. The data related to plant growth was analyzed using a Linear Mixed Model, while final biomass and post-harvest soil analysis were conducted using Factorial ANOVA. There were differences in the quality of compost from different sources. While Padang Tegal met all the SNI requirements, others failed to meet certain criteria including high levels of organic carbon, organic matter, pH value, C/N ratio, or foreign particles. Organic carbon ranged from 26.13% to 34.51%, total nitrogen from 0.72% to 2.84%, and C/N ratio from 11.67 to 47.55. Plant growth responses were strongly time-dependent. Compost dose significantly affected plant height, number of leaves, and stem diameter, whereas SPAD response was influenced by compost source and its interactions with dose and observation time. However, fresh and dry biomass were not significantly affected by compost source, dose, or their interaction. Post-harvest soil organic carbon, total nitrogen, and C/N ratio were significantly affected by compost source, dose, and their interaction. These findings indicate that composts from local waste management facilities differ in quality and produce time-dependent soil-plant responses. Further studies with larger replication and direct measurements of nutrient dynamics are needed before broader agronomic recommendations can be made.